2011
DOI: 10.1590/s1808-86942011000500016
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and participation restrictions, a study in elderly

Abstract: Accordi ng to the IBGE, Brazil had 21 million elderly persons in 2008.Objective: To study the effects of speech therapy -fitting of hearing aids -on the quality of life of elderly persons and restriction of participation according to sex and age.Material and Method: 50 elderly subjects, 23 females and 27 males, were allocated to Group 1 and Group 2, and were assessed with questionnaires (HHIE and SF 36) before and one year after fitting hearing aids; subjects were monitored every two months. Results:The HHIE S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…A research applied the same questionnaire to 29 elderly, before the use of the hearing aid and after one year of use, resulting in a significant reduction in the restriction of participation after the use of hearing aid, in the group studied (24) . Another study, also similar, demonstrated that the elderly showed reduction in the self-perception of the restrictions of participation after the use of the hearing aid, attributing this improvement to the adaptation and the use of hearing aids (25) .…”
Section: Discussionmentioning
confidence: 72%
“…A research applied the same questionnaire to 29 elderly, before the use of the hearing aid and after one year of use, resulting in a significant reduction in the restriction of participation after the use of hearing aid, in the group studied (24) . Another study, also similar, demonstrated that the elderly showed reduction in the self-perception of the restrictions of participation after the use of the hearing aid, attributing this improvement to the adaptation and the use of hearing aids (25) .…”
Section: Discussionmentioning
confidence: 72%
“…While verifying the studies that were selected (Table 1), it was noted that seven studies utilized the hearing handicap protocols only in the adult population (8,9,11,16,18,23) . In 12 studies, the sample was composed exclusively of the elderly (6,10,(13)(14)(15)17,22,(25)(26)(27)(28)(29) ; while the remaining papers, seven (3,7,12,(19)(20)(21)24) , evaluated hearing handicaps in both adults and the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies selected (3,7,8,17,20,29) , the questionnaires for hearing handicap were utilized to evaluate the intervention plan and if the aural rehabilitation were effective in decreasing the disabilities and handicaps. As a result, it was noted that the use of the personal hearing amplification devices aided in the reduction of the perception of handicaps and hearing difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…One way to lessen the impact of hearing loss in a person is the use of hearing aids (HA) (2) which is also a therapeutic tool in the audiological maintenance of tinnitus (3,4) . Tinnitus is considered a perception of sound without its presence in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the authors recommend the adaptation of hearing aids in patients with hearing loss accompanied by tinnitus as an alternative to intervention (2,3,9) . Many times speech perception is associated with tinnitus and may be harmed by this symptom.…”
Section: Introductionmentioning
confidence: 99%